2005
DOI: 10.1002/pssb.200440037
|View full text |Cite
|
Sign up to set email alerts
|

The influence of Sc substitution on some physical properties of ScxHo1–xNi2 solid solutions

Abstract: Results of X-ray diffraction analysis, magnetization measurements, magnetic susceptibility, electrical resistivity, and heat capacity performed on polycrystalline Sc x Ho 1-x Ni 2 (0 ≤ x ≤ 1) solid solutions are reported. It was found that they crystallize with the formation of the C15 type Laves-phase superstructure. At low temperatures (below 20 K), the Sc x Ho 1-x Ni 2 solid solutions with 0 ≤ x ≤ 0.6 are ferromagnets. At higher temperatures, all solid solutions are Curie -Weiss paramagnets. Temperature dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
2
3
0
Order By: Relevance
“…However, some authors [3,4] have reported the possible existence of a residual magnetic moment at nickel atoms. Moreover our recent investigations confirmed this assumption, namely, we have found that magnetic moments in some poorly diluted solid solutions, such as Lu 0.2 Ho 0.8 Ni 2 [5] and Sc 0.2 Ho 0.8 Ni 2 [6], are higher than that due to only holmium atoms. This also suggests the existence of a residual magnetic moment at the nickel atoms.…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…However, some authors [3,4] have reported the possible existence of a residual magnetic moment at nickel atoms. Moreover our recent investigations confirmed this assumption, namely, we have found that magnetic moments in some poorly diluted solid solutions, such as Lu 0.2 Ho 0.8 Ni 2 [5] and Sc 0.2 Ho 0.8 Ni 2 [6], are higher than that due to only holmium atoms. This also suggests the existence of a residual magnetic moment at the nickel atoms.…”
Section: Introductionsupporting
confidence: 53%
“…This superstructure, corresponding to space group F43m and having a doubled lattice parameter, is characterized by ordered vacancies at the rare earth metal sites. Furthermore, our previous studies confirmed that A x Ho 1−x Ni 2 (A = Y [9], Lu [5], Sc [6]) solid solutions crystallize with the formation of the Laves-phase superstructure (F 43m e.g. ).…”
Section: Structural Investigationmentioning
confidence: 55%
“…However, the existence of the residual magnetic moment on nickel resulting in an increase of the total magnetic moment has been reported [10,11]. Our recent study confirmed this assumption: the magnetic moments of poorly diluted Ho 0.9 La 0.1 Ni 2 , Ho 0.85 La 0.15 Ni 2 [12], Ho 0.8 Lu 0.2 Ni 2 [13] and Ho 0.8 Sc 0.2 Ni 2 [14] solid solutions have been found to be higher than those due to holmium atoms only. In the R-Ni alloys, the main sources of the magnetic moment are electrons located in the unfilled f-level of lanthanide atoms.…”
Section: Introductionsupporting
confidence: 71%
“…x ≤ 0.8 but in the case of Ho 1-x La x Ni 2 similar to the Ho 1-x Y x Ni 2 and Ho 1-x Sc x Ni 2 system [20,21] the ferromagnetic order disappears after substitution of lanthanum in place of more than 80 % of holmium.…”
Section: Magnetic Measurementsmentioning
confidence: 89%